Frontispiece: Biomolecular Assemblies Combining Two Orthogonal Copper‐Mediated Ligations in a One‐Pot Reaction. Issue 16 (13th April 2015) - Grassin, Adrien; Claron, Michaël; Boturyn, Didier
<x xml:space="preserve">Abstract</x> Click Chemistry Biomolecular assemblies are essential to construct macromolecules encompassing several biorelevant functions. A new method that involves two orthogonal copper‐mediated ligations of azide with alkyne, and amine with thioacid, was developed for the ligation of three different chemical components. Interestingly, it was observed that the ligation of azide with alkyne was found to be faster than the ligation of amine with thioacid. For more details, see the Communication by D. Boturyn et al. on page 6022 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>